Shaped activated carbon as well as preparation method and application thereof

By kneading, mixing and forming a high-specific surface area activated carbon powder with a variety of binders and reinforcers, high-strength, low-powder wear activated carbon is prepared, which solves the problems of low specific surface area and insufficient strength in the existing activated carbon molding process. , meets the use needs of automobile charcoal canisters.

CN119461369APending Publication Date: 2025-02-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1

Patent Information

Application Number
CN202411954711.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing activated carbon molding process has problems of low specific surface area and insufficient strength, especially when used in automotive carbon tanks, the powder wear is severe, which affects the normal operation of the equipment.

Method used

Use activated carbon powder with high specific surface area and narrow pore size distribution to knead and mix with cellulose binder, emulsion binder, reinforcer, lubricant and solvent. Through the mud training and molding process, high specific surface area and high ball plate strength are prepared. And the pulverization of columnar or honeycomb activated carbon with less wear.

Benefits of technology

The high specific surface area, ball strength and butane working capacity of activated carbon are improved, while reducing the dust wear rate and meeting the needs of use in automotive charcoal cans.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215573360000131
    Figure BDA0005215573360000131
Patent Text Reader

Abstract

The invention relates to shaped activated carbon, a preparation method and application, in particular to the field of activated carbon preparation, and the shaped activated carbon comprises activated carbon powder, a cellulose binder, an emulsion binder, a reinforcing agent, a lubricant and a solvent. According to the shaped activated carbon provided by the invention, the activated carbon with high specific surface area and narrow pore size distribution, the binder and the additive are used for preparing columnar or honeycomb-shaped activated carbon with high specific surface area, high ball disc strength, high butane working capacity and relatively small pulverization wear, and the shaped activated carbon can be used for adsorbing and / or storing gasoline steam in an automobile carbon tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of activated carbon preparation, and in particular to a shaped activated carbon, a preparation method and an application thereof, and in particular to a shaped activated carbon, a preparation method and an application thereof. Background Art

[0002] At present, activated carbon is a product obtained by carbonization and activation using sawdust, fruit shells, coal and other raw materials. Due to its highly developed pore structure, ultra-large specific surface area, stable performance, easy regeneration and other advantages, it is widely used in chemical production, environmental protection and other fields.

[0003] In the carbonization and activation process, in order to make the reaction more complete, the raw materials are usually crushed into small particles, then fully mixed with the activator, and then put into the rotary kiln to complete the carbonization and activation. The activated carbon obtained through this process needs to be crushed, screened, and formed again to meet actual needs.

[0004] For example, CN105293491A discloses a method for preparing and molding activated carbon activated by solid KOH, wherein sodium aluminate, sodium silicate, and KOH are used to form a binder, and activated carbon powder is added after the KOH is completely deliquesced, mixed and kneaded, extruded, and dried to obtain molded activated carbon particles. Although this method can conveniently obtain molded activated carbon, the strongly alkaline KOH will remain in the carbon, making the granular activated carbon alkaline, which is not applicable in many usage scenarios.

[0005] CN116730339A discloses a novel harmless preparation device and process for wood columnar activated carbon, wherein the activated carbon material is mixed with one or more binders such as asphalt powder, coal tar, kaolin, and starch, added to an extruder to extrude into a column, and then dried to obtain columnar activated carbon. This is the most common post-forming process for preparing columnar activated carbon, and a similar process is also disclosed in CN107555431A. The key to this process is to select a suitable binder and regulate the appropriate mixing conditions so that the prepared columnar activated carbon can have a higher strength and its own pore structure will not be blocked by the binder.

[0006] Activated carbon for automobile canisters is a type of activated carbon filled in automobile canisters for the purpose of absorbing and storing gasoline vapor. It is usually in the shape of a column or honeycomb. The specific surface area of ​​the activated carbon is usually around 1500 m 2 / g or more, the ball-disc strength is more than 80%, and the ASTM butane working capacity is 0.3g / g. More importantly, when the car starts, the gasoline vapor stored in the activated carbon in the charcoal canister will be purged out and enter the engine through the solenoid valve, which puts higher requirements on the pulverization and wear of the activated carbon in the charcoal canister. The degree of pulverization and wear is high, and the tiny particles of activated carbon will enter the solenoid valve with the airflow, and even enter the engine. In the long run, the solenoid valve will be damaged at the least, and the engine will be damaged at the worst. However, the current national standard does not stipulate the pulverization and wear of activated carbon. Therefore, this issue has not received the attention of activated carbon developers. Automobile OEMs usually refer to the US ASTM standard and set the dust wear coefficient index, which is required to be no higher than 80mg / min. This data is still challenging for some domestic activated carbons.

[0007] Using the post-molding process, the carbon powder that meets the requirements is simply mixed with conventional binders such as kaolin, clay, diatomaceous earth, etc. and then extruded to obtain columnar or honeycomb activated carbon. Usually, the specific surface area is reduced due to the pore blocking of the binder, or the strength of the ball disc is low due to insufficient addition of the binder, and these conventional binders cannot solve the problem of powder wear. Therefore, it is urgent to develop a new activated carbon molding process to meet the demand for activated carbon in automotive canisters. Summary of the invention

[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing shaped activated carbon and the use of the obtained shaped activated carbon, so as to solve the defects of low specific surface area and insufficient strength of the current shaped activated carbon.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a shaped activated carbon, the shaped activated carbon comprising:

[0011] Activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent.

[0012] The shaped activated carbon provided by the present invention is prepared by mixing activated carbon with high specific surface area and narrow pore size distribution with a binder and an additive to obtain columnar or honeycomb activated carbon with high specific surface area, high ball-disc strength, high butane working capacity and less pulverization and wear, which can be used for adsorbing and / or storing gasoline vapor in automobile carbon cans.

[0013] As a preferred technical solution of the present invention, the shaped activated carbon comprises, by weight:

[0014] 0.9-1.1 parts of activated carbon powder, 0.05-0.2 parts of cellulose binder, 0.03-0.2 parts of emulsion binder, 0.05-0.3 parts of reinforcing agent, 0.005-0.05 parts of lubricant and 1-2 parts of solvent.

[0015] As a preferred technical solution of the present invention, the BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g.

[0016] Preferably, the pore size of the activated carbon powder is 2-6 nm.

[0017] Preferably, the particle size of the activated carbon is ≤74 μm.

[0018] As a preferred technical solution of the present invention, the cellulose binder includes one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose.

[0019] Preferably, the viscosity of the cellulose binder is 10000-200000 mPa·s.

[0020] As a preferred technical solution of the present invention, the emulsion adhesive includes an acrylic acid solution.

[0021] Preferably, the solid content of the emulsion binder is 10-90% by mass.

[0022] As a preferred technical solution of the present invention, the reinforcing agent includes silica sol.

[0023] Preferably, the particle size of the solid particles in the silica sol is 6-50 nm.

[0024] Preferably, the solid content of the silica sol is 10-90% by mass.

[0025] Preferably, the pH value of the enhancer is 8-10.

[0026] Preferably, the lubricant comprises one or a combination of at least two of edible vegetable oil, white oil or glycerol.

[0027] Preferably, the kinematic viscosity of the lubricant is ≤5m 2 / s.

[0028] In a second aspect, the present invention provides a method for preparing the shaped activated carbon as described in the first aspect, the preparation method comprising:

[0029] The activated carbon powder, the cellulose binder, the emulsion binder, the reinforcing agent, the lubricant and the solvent are kneaded and mixed to obtain a mixture;

[0030] The mixture is sequentially kneaded and formed to obtain shaped activated carbon.

[0031] Preferably, the BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g.

[0032] Preferably, the pore size of the activated carbon powder is 2-6 nm.

[0033] Preferably, the particle size of the activated carbon is ≤74 μm.

[0034] Preferably, the cellulose binder includes one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose.

[0035] Preferably, the viscosity of the cellulose binder is 10000-200000 mPa·s.

[0036] Preferably, the emulsion binder comprises an acrylic acid solution.

[0037] Preferably, the solid content of the emulsion binder is 10-90% by mass.

[0038] Preferably, the reinforcing agent comprises silica sol.

[0039] Preferably, the particle size of the solid particles in the silica sol is 6-50 nm.

[0040] Preferably, the solid content of the silica sol is 10-90% by mass.

[0041] Preferably, the pH value of the enhancer is 8-10.

[0042] Preferably, the lubricant comprises one or a combination of at least two of edible vegetable oil, white oil or glycerol.

[0043] Preferably, the kinematic viscosity of the lubricant is ≤5m 2 / s.

[0044] As a preferred technical solution of the present invention, the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent in the mixture is (0.9-1.1):(0.05-0.2):(0.03-0.2):(0.05-0.3):(0.005-0.051):(1-2).

[0045] Preferably, the kneading and mixing temperature is 20-40°C.

[0046] Preferably, the kneading and mixing time is 0.25-2h.

[0047] Preferably, the temperature of the clay kneading is 20-40°C.

[0048] Preferably, the rotation speed of the mud kneading is 10-15r / min.

[0049] Preferably, the time for kneading the mud is 10-30 minutes.

[0050] Preferably, the mud kneading is performed at least 3 times.

[0051] Preferably, the shaping comprises extrusion shaping.

[0052] Preferably, the extrusion molding method includes one of single-screw extrusion, twin-screw extrusion or hydraulic extrusion.

[0053] In a third aspect, the present invention provides a use of the shaped activated carbon as described in the first aspect, the use comprising:

[0054] The shaped activated carbon is used in an automobile carbon canister.

[0055] Compared with the prior art solutions, the present invention has the following beneficial effects:

[0056] The molding method provided by the present invention uses a plurality of adhesives and reinforcing agents to form powdered activated carbon into columnar carbon of a specified particle size and shape according to demand while ensuring that the pore structure and specific surface area of ​​the raw activated carbon powder are not affected. More importantly, the addition of an emulsion adhesive such as an acrylic emulsion will cause the molded carbon to quickly form a transparent film layer on the surface during the drying process, thereby preventing the molded carbon from "falling powder", and completely solving the problem of severe powdering and wear of the molded carbon and poor butane adsorption effect when using conventional adhesives. The butane working capacity of the molded activated carbon of the present invention is ≥0.40g / g, the ball-disc strength is ≥93%, and the dust wear rate is ≤33mg / min. DETAILED DESCRIPTION

[0057] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0058] This embodiment provides a shaped activated carbon, the shaped activated carbon comprising:

[0059] Activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent.

[0060] Specifically, the shaped activated carbon comprises, by weight:

[0061] 0.9-1.1 parts of activated carbon powder, 0.05-0.2 parts of cellulose binder, 0.03-0.2 parts of emulsion binder, 0.05-0.3 parts of reinforcing agent, 0.005-0.05 parts of lubricant and 1-2 parts of solvent.

[0062] Wherein, the BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g.

[0063] Wherein, the pore size of the activated carbon powder is 2-6nm.

[0064] Wherein, the particle size of the activated carbon is ≤74 μm.

[0065] Wherein, the cellulose binder includes one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose.

[0066] Wherein, the viscosity of the cellulose binder is 10000-200000 mPa·s.

[0067] Wherein, the emulsion adhesive comprises acrylic acid solution.

[0068] Wherein, the solid content of the emulsion binder is 10-90% by mass.

[0069] Wherein, the reinforcing agent includes silica sol.

[0070] Wherein, the particle size of the solid particles in the silica sol is 6-50nm.

[0071] Wherein, the solid content of the silica sol is 10-90% by mass.

[0072] Wherein, the pH value of the enhancer is 8-10.

[0073] Wherein, the lubricant includes one or a combination of at least two of edible vegetable oil, white oil or glycerol.

[0074] Wherein, the kinematic viscosity of the lubricant is ≤5m 2 / s.

[0075] The solvent includes water, ethanol and other commonly used solvents in the art.

[0076] The specific preparation process is as follows, including:

[0077] The activated carbon powder, the cellulose binder, the emulsion binder, the reinforcing agent, the lubricant and the solvent are kneaded and mixed to obtain a mixture;

[0078] The mixture is sequentially kneaded and formed to obtain shaped activated carbon.

[0079] Wherein, the BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g, for example, it can be 1500m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g, 2400m 2 / g or 2500m 2 / g, etc., but not limited to the listed values, other values ​​not listed within the range also meet the requirements.

[0080] Wherein, the pore size of the activated carbon powder is 2-6nm.

[0081] Wherein, the particle size of the activated carbon is ≤74 μm.

[0082] In the present invention, the limitation on particle size or particle diameter refers to the aggregate of particles of a single particle diameter within a limited range, or the aggregate of all particles within a certain particle diameter range.

[0083] Wherein, the cellulose binder includes one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose.

[0084] For example, the combination of cellulose binders may be selected as a combination of hydroxymethyl cellulose and hydroxyethyl cellulose, a combination of hydroxyethyl cellulose and carboxymethyl cellulose, a combination of carboxymethyl cellulose and hydroxypropyl methyl cellulose, and the like.

[0085] Wherein, the viscosity of the cellulose binder is 10000-200000 mPa·s, for example, it can be 10000 mPa·s, 20000 mPa·s, 40000 mPa·s, 60000 mPa·s, 80000 mPa·s, 100000 mPa·s, 120000 mPa·s, 140000 mPa·s, 160000 mPa·s, 180000 mPa·s or 200000 mPa·s, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0086] Wherein, the emulsion adhesive comprises acrylic acid solution.

[0087] The solid content of the emulsion binder is 10-90% by mass, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0088] Wherein, the reinforcing agent includes silica sol.

[0089] Wherein, the particle size of the solid particles in the silica sol is 6-50nm.

[0090] The solid content of the silica sol is 10-90% by mass, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0091] The pH value of the enhancer is 8-10, for example, 8, 8.5, 9, 9.5 or 10, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0092] Wherein, the lubricant includes one or a combination of at least two of edible vegetable oil, white oil or glycerol.

[0093] In the present invention, the edible vegetable oil used includes edible peanut oil and / or edible sunflower oil.

[0094] Exemplarily, the combination of lubricants used can be selected as: a combination of edible peanut oil and white oil, a combination of edible sunflower oil and glycerin, a combination of glycerin and white oil, and the like.

[0095] Wherein, the kinematic viscosity of the lubricant is ≤5m 2 / s, for example, 5m 2 / s、4.5m 2 / s、4m 2 / s、3.5m 2 / s、3m 2 / s, 2.5m 2 / s、2m 2 / s、1.5m 2 / s or 1m 2 / s, etc., but not limited to the listed values, other values ​​not listed in the range also meet the requirements.

[0096] Among them, the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent in the mixture is (0.9-1.1):(0.05-0.2):(0.03-0.2):(0.05-0.3):(0.005-0.051):(1-2), for example, it can be 0.9:0.05:0.03:0.05:0.005:1, 1.1:0.2:0.2:0.3:0.051:2, 1:0.1:0.15:0.2:0.03:1, 1:0.15:0.1:0.1:0.01:1.5 or 1:0.1:0.1:0.15:0.04:1, etc., but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0097] Wherein, the kneading and mixing temperature is 20-40°C, for example, it can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, but is not limited to the listed values, and other unlisted values ​​within this range also meet the requirements.

[0098] The kneading and mixing time is 0.25-2h, for example, it can be 0.25h, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, but is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0099] The temperature of the clay kneading is 20-40°C, for example, 20°C, 25°C, 30°C, 35°C or 40°C, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0100] Among them, the rotation speed of the clay kneading is 10-15r / min, for example, it can be 10r / min, 11r / min, 12r / min, 13r / min, 14r / min or 15r / min, but it is not limited to the listed values, and other unlisted values ​​within the range also meet the requirements.

[0101] The time for kneading the clay is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min, etc., but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0102] The kneading is performed at least three times, for example, 3 times, 4 times, 5 times, 6 times or 7 times, but is not limited to the listed values, and other values ​​not listed within the range also meet the requirements.

[0103] In the present invention, the time for kneading the clay is the time for a single operation.

[0104] In the present invention, the shapes of column, granule, honeycomb, etc. can be selected according to actual needs.

[0105] Wherein, the molding includes extrusion molding.

[0106] Wherein, the extrusion molding method includes one of single-screw extrusion, twin-screw extrusion or hydraulic extrusion.

[0107] Furthermore, the present invention provides the use of the shaped activated carbon as described above, the use comprising:

[0108] The shaped activated carbon is used in an automobile carbon canister.

[0109] Further, in order to illustrate the good performance of the activated carbon prepared by the present invention, the following practical examples are used for illustrative purposes, as follows:

[0110] Example 1

[0111] This embodiment provides a method for forming activated carbon, the method comprising the following steps:

[0112] (1) Take 1 portion with a specific surface area of ​​1500m 2 / g, with a pore size distribution of 2-6nm as the main material and a particle size of about 2 mesh, after grinding and sieving, 0.98 parts of raw material activated carbon powder under 200 mesh sieve were obtained;

[0113] (2) the raw material activated carbon powder sieved in step (1) is mixed with 0.1 part of hydroxymethyl cellulose with a viscosity of 100000 mPa·s, 0.077 part of acrylic emulsion with a solid content of 40%, 0.15 part of silica sol solution with a particle size range of 6-10 nm, a solid content of 40%, and a pH of 9.0, and 0.05 part of a kinematic viscosity of 30 mm 2 / s of edible peanut oil and 1 part of water (the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent is 1:0.102:0.079:0.153:0.051:1.02) are fully mixed, then transferred to a kneader and kneaded at 25°C for 0.5h;

[0114] (3) The kneaded mixture is placed in a mud mill for 4 times (the temperature of a single mud milling is 30°C, the rotation speed is 12 r / min, and the time is 20 min), and then transferred to a hydraulic extruder. A single-layer through-hole sieve plate with a pore size of 2.2 mm is selected for extrusion. The pellets are cut into 5 mm lengths and placed in an oven for thorough drying to obtain columnar activated carbon with a length of 5±5% mm and a diameter of 2.0±5% mm.

[0115] Example 2

[0116] This embodiment provides a method for forming activated carbon, the method comprising the following steps:

[0117] (1) Take 1 portion with a specific surface area of ​​1600m 2 / g, with a pore size distribution of 2-6nm as the main material and a particle size of about 5 mesh, after grinding and sieving, 0.9 parts of raw material activated carbon powder under 300 mesh sieve were obtained;

[0118] (2) the raw material activated carbon powder sieved in step (1) is mixed with 0.11 parts of hydroxypropyl methylcellulose with a viscosity of 200000 mPa·s, 0.056 parts of acrylic emulsion with a solid content of 30%, 0.17 parts of silica sol solution with a particle size range of 6-10 nm, a solid content of 30%, and a pH of about 8.0, and 0.011 parts of a kinematic viscosity of 40 mm 2 / s of edible sesame oil and 1.2 parts of water (the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent is 1:0.122:0.062:0.189:0.012:1.33) are fully mixed, then transferred to a kneader and kneaded at 30°C for 0.4h;

[0119] (3) The kneaded mixture is placed in a mud mill for 3 times (the temperature of a single mud milling is 35°C, the rotation speed is 14r / min, and the time is 15min), and then transferred to a hydraulic extruder. A single-layer through-hole sieve plate with a pore size of 2.2mm is selected for extrusion. The pellets are cut into 5mm lengths and placed in an oven for thorough drying to obtain columnar activated carbon with a length of 5±5%mm and a diameter of 2.0±5%mm.

[0120] Example 3

[0121] This embodiment provides a method for forming activated carbon, the method comprising the following steps:

[0122] (1) Take 1 portion with a specific surface area of ​​1500m 2 / g, with a pore size distribution of 2-6nm as the main material and a particle size of about 2 mesh, after grinding and sieving, 0.98 parts of raw material activated carbon powder under 200 mesh sieve were obtained;

[0123] (2) the raw material activated carbon powder sieved in step (1) is mixed with 0.05 parts of hydroxypropyl methylcellulose with a viscosity of 200000 mPa·s, 0.03 parts of acrylic emulsion with a solid content of 30%, 0.27 parts of silica sol solution with a particle size range of 6-10 nm, a solid content of 30%, and a pH of about 8.0, and 0.02 parts of a kinematic viscosity of 40 mm 2 / s of edible sesame oil and 1.8 parts of water (the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent is 1:0.051:0.031:0.276:0.02:1.84) are fully mixed, then transferred to a kneader and kneaded at 20°C for 2h;

[0124] (3) The kneaded mixture is placed in a mud mill for 6 times (the temperature of a single mud milling is 20°C, the rotation speed is 15 r / min, and the time is 30 min), and then transferred to a hydraulic extruder. A single-layer through-hole sieve plate with a pore size of 2.2 mm is selected for extrusion. The pellets are cut into 5 mm lengths and placed in an oven for thorough drying to obtain columnar activated carbon with a length of 5±5% mm and a diameter of 2.0±5% mm.

[0125] Example 4

[0126] This embodiment provides a method for forming activated carbon, the method comprising the following steps:

[0127] (1) Take 1 portion with a specific surface area of ​​1600m 2 / g, with a pore size distribution of 2-6nm as the main material and a particle size of about 5 mesh, after grinding and sieving, 0.9 parts of raw material activated carbon powder under 300 mesh sieve were obtained;

[0128] (2) the raw material activated carbon powder under the sieve after the sieving in step (1) is mixed with 0.18 parts of hydroxypropyl methylcellulose with a viscosity of 200000 mPa·s, 0.18 parts of acrylic emulsion with a solid content of 30%, 0.05 parts of silica sol solution with a particle size range of 6-10 nm, a solid content of 30%, and a pH of about 8.0, and 0.005 parts of a kinematic viscosity of 40 mm 2 / s of edible sesame oil and 1.5 parts of water (the mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent is 1:0.2:0.2:0.056:0.0056:1.67) are fully mixed, then transferred to a kneader and kneaded at 40°C for 0.25h;

[0129] (3) The kneaded mixture is placed in a mud mill for 5 times (the temperature of a single mud milling is 40°C, the rotation speed is 10 r / min, and the time is 10 min), and then transferred to a hydraulic extruder. A single-layer through-hole sieve plate with a pore size of 2.2 mm is selected for extrusion. The pellets are cut into 5 mm lengths and placed in an oven for thorough drying to obtain columnar activated carbon with a length of 5±5% mm and a diameter of 2.0±5% mm.

[0130] Comparative Example 1

[0131] The only difference from Example 1 is that no acrylic emulsion is added.

[0132] Comparative Example 2

[0133] The only difference from Example 1 is that no reinforcing agent is added.

[0134] Comparative Example 3

[0135] The only difference from Example 1 is that the acrylic emulsion is replaced by an equal amount of styrene acrylic emulsion with the same solid content.

[0136] Comparative Example 4

[0137] The only difference from Example 1 is that the acrylic emulsion is replaced by an equal amount of pure acrylic emulsion with the same solid content.

[0138] The specific surface area of ​​the activated carbon materials formed in the embodiments and comparative examples was tested by the following method:

[0139] The pore structure of the material was determined using the Kubo-X1000 pore size and specific surface area analyzer produced by Beijing Biode Electronics Co., Ltd. The specific surface area of ​​the material was calculated using the BET method by testing the N2 adsorption-desorption isotherm of the material.

[0140] The butane working capacity of the activated carbon materials formed in the embodiments and comparative examples was tested, and the testing method was based on the national standard GB / T20449-2006 "Test method for butane working capacity of activated carbon".

[0141] The activated carbon materials formed in the examples and comparative examples were tested for ball-on-disk strength, and the test method was based on the national standard GB / T20451-2006 “Activated carbon ball-on-disk strength test method”.

[0142] The pulverization wear test was carried out in accordance with the American ASTM D 5159-9 "Standard Test Method for Pulverization Wear of Granular Activated Carbon".

[0143] All the above test results are listed in Table 1.

[0144] Table 1

[0145]

[0146] As can be seen from Table 1, Examples 1-4 all show that there is no obvious change in the specific surface area of ​​the activated carbon before and after molding, and the butane working capacity, ball-disc strength, and dust wear coefficient of the shaped activated carbon are all excellent.

[0147] However, in Comparative Example 1, due to the lack of emulsion binder, only cellulose binder is relied on, which cannot solve the problem of powder loss of shaped carbon, thus causing its dust wear coefficient to exceed the industry index. The role played by acrylic emulsion binder in the molding process is mainly to form an ultra-thin film on the surface of the shaped carbon, which can solve the problem of powder loss, and will not affect the diffusion and adsorption and desorption of n-butane or gasoline vapor due to the thickness being too thick and the film formation being too uniform. The reinforcing agent missing in Comparative Example 2 is a key additive to ensure the strength of the shaped carbon, so the ball plate strength does not meet the requirements. Comparative Examples 3 and 4 use other common emulsions to replace acrylic emulsions. These two emulsions have good film-forming properties and low film-forming temperatures, resulting in rapid film formation during the kneading process. It is difficult for other components to be mixed evenly with carbon powder, which in turn affects the strength and dust wear of the shaped carbon. More importantly, the film-forming property is too good and the film formation is too uniform, resulting in n-butane gas not being easy to diffuse on the surface of the shaped carbon, showing that the butane working capacity is low, so it is crucial to choose a suitable emulsion binder.

[0148] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0149] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0150] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A shaped activated carbon, characterized in that: The shaped activated carbon comprises: Activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent.

2. The shaped activated carbon according to claim 1, characterized in that The shaped activated carbon comprises, by weight: 0.9-1.1 parts of activated carbon powder, 0.05-0.2 parts of cellulose binder, 0.03-0.2 parts of emulsion binder, 0.05-0.3 parts of reinforcing agent, 0.005-0.05 parts of lubricant and 1-2 parts of solvent.

3. The shaped activated carbon according to claim 1 or 2, characterized in that: The BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g; Preferably, the pore size of the activated carbon powder is 2-6 nm; Preferably, the particle size of the activated carbon is ≤74 μm.

4. The shaped activated carbon according to any one of claims 1 to 3, characterized in that: The cellulose binder includes one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose; Preferably, the viscosity of the cellulose binder is 10000-200000 mPa·s.

5. The shaped activated carbon according to any one of claims 1 to 4, characterized in that: The emulsion binder includes an acrylic acid solution; Preferably, the solid content of the emulsion binder is 10-90% by mass.

6. The shaped activated carbon according to any one of claims 1 to 5, characterized in that: The reinforcing agent includes silica sol; Preferably, the particle size of the solid particles in the silica sol is 6-50 nm; Preferably, the solid content of the silica sol is 10-90% by mass percentage; Preferably, the pH value of the enhancer is 8-10; Preferably, the lubricant comprises one or a combination of at least two of edible vegetable oil, white oil or glycerol; Preferably, the kinematic viscosity of the lubricant is ≤5m 2 / s.

7. A method for preparing shaped activated carbon, characterized in that: The preparation method comprises: The activated carbon powder, the cellulose binder, the emulsion binder, the reinforcing agent, the lubricant and the solvent are kneaded and mixed to obtain a mixture; The mixture is sequentially kneaded and formed to obtain shaped activated carbon.

8. The preparation method according to claim 7, characterized in that: The BET specific surface area of ​​the activated carbon powder is ≥1500m 2 / g; Preferably, the pore size of the activated carbon powder is 2-6 nm; Preferably, the particle size of the activated carbon is ≤74 μm; Preferably, the cellulose binder comprises one or a combination of at least two of hydroxymethyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose or hydroxypropyl methyl cellulose; Preferably, the viscosity of the cellulose binder is 10000-200000 mPa·s; Preferably, the emulsion binder comprises an acrylic acid solution; Preferably, the solid content of the emulsion binder is 10-90% by mass percentage; Preferably, the reinforcing agent comprises silica sol; Preferably, the particle size of the solid particles in the silica sol is 6-50 nm; Preferably, the solid content of the silica sol is 10-90% by mass percentage; Preferably, the pH value of the enhancer is 8-10; Preferably, the lubricant comprises one or a combination of at least two of edible vegetable oil, white oil or glycerol; Preferably, the kinematic viscosity of the lubricant is ≤5m 2 / s.

9. The preparation method according to claim 7 or 8, characterized in that: The mass ratio of activated carbon powder, cellulose binder, emulsion binder, reinforcing agent, lubricant and solvent in the mixture is (0.9-1.1):(0.05-0.2):(0.03-0.2):(0.05-0.3):(0.005-0.051):(1-2); Preferably, the kneading and mixing temperature is 20-40°C; Preferably, the kneading and mixing time is 0.25-2h; Preferably, the temperature of the mud kneading is 20-40°C; Preferably, the rotation speed of the mud kneading is 10-15r / min; Preferably, the time for kneading the mud is 10-30 minutes; Preferably, the mud kneading is performed at least 3 times; Preferably, the forming comprises extrusion forming; Preferably, the extrusion molding method includes one of single-screw extrusion, twin-screw extrusion or hydraulic extrusion.

10. A use of the shaped activated carbon according to any one of claims 1 to 6, characterized in that: The uses include: The shaped activated carbon is used in an automobile carbon canister.

Citation Information

Patent Citations

  • KOH solid activated active carbon preparation and forming method

    CN105293491A

  • Bamboo columnar activated carbon as well as preparation method and application thereof

    CN107555431A

Cited By

  • Anti-pulverization activated carbon and preparation method thereof

    CN120364700A